Cultivating trust in technology‐mediated sustainable agricultural research. (13th January 2022) - Raturi, Ankita; Thompson, Jennifer J.; Ackroyd, Victoria; Chase, Carlene A.; Davis, Brian W.; Myers, Robert; Poncet, Aurelie; Ramos‐Giraldo, Paula; Reberg‐Horton, Chris; Rejesus, Roderick; Robertson, Alison; Ruark, Matthew D.; et al.
Abstract: We formed the Precision Sustainable Agriculture (PSA) team to conduct interdisciplinary research and technology development to improve adoption and practice of knowledge‐intensive sustainable agricultural practices such as cover cropping. In this paper, we share our approach to cultivating trust among diverse stakeholders (researchers, farmers, extensionists, agricultural and information specialists, private and public entities) vested in agricultural data collection, management, and use. Our trust framework describes how we aim to be trusted with data (through preserving privacy and increasing stakeholder agency) and trusted in the process (through practicing transparency and accountability). It is operationalized through a series of social and technical infrastructures. Our project governance, stakeholder engagement tools and activities, and technology development methods aim to promote transparency and accountability in our process. We use a maturity model to govern data acquisition to ensure that only robust, privacy‐preserving technologies are deployed on our partner farms and describe evolving mechanisms for handling data with varying sensitivity. Finally, we share preliminary work aimed at anticipating data use, and identify challenges on the horizon for cultivating trust in agricultural technologies and data‐driven agriculture. Core Ideas: Sustainable agriculture is information intensive, requiring data sharing among many actors. Trust can be mediated through technology, but only with the input of all data stakeholders. Practicing privacy preserving strategies and increasing stakeholder agency increase trust. Transparency and accountability can aid in fostering trust in the process of data management. Cultivating trust is critical for success in data‐driven and sustainable agriculture.